Bibliometric Insights on Mangrove Actinobacteria's Secondary Metabolites as Antibiotics Using VOSviewer - Sakaroni, Rubiyatna; Listantia, Nora; Ningthias, Dyah Puspitasari (Jurnal Biologi Tropis, 2024)
Secondary metabolites from actinobacteria have been known to have many potentials as antioxidants, antibiotics, anti-cancer, and others. Various studies have been conducted and published regarding the findings of the potential of actinobacteria. This study aims to determine the development of research related to the potential of actinobacteria originating from mangrove areas and their secondary metabolites as natural antibiotics with bibliometric methods assisted by the VOS Viewer application. The articles used in this study are articles published from 2014 to 2024 and taken from the PubMed database. A total of 78 articles analyzed with VOS Viewer showed that over the past decade, the development of research on this topic still revolves around actinobacteria, microbial sensitivity tests, anti-bacterial agents, and Streptomyces as indicated by the high occurrence of these words in the titles and abstracts of the articles analyzed. The potential for research development can be directed at antineoplastic agents, cell proliferation, and mass spectrometry because the use of these terms is still minimal. However, analysis using other databases is needed as a comparison to get clearer results related to the development of research on the potential of actinobacteria derived from mangroves and their secondary metabolites as antibitoics.